2022
DOI: 10.1108/jeas-10-2021-0204
|View full text |Cite
|
Sign up to set email alerts
|

Intention to adopt cryptocurrency: a robust contribution of trust and the theory of planned behavior

Abstract: PurposeAt present, the adoption of cryptocurrency investment has brought consideration to the globe. The present paper attempts to investigate the intention to adopt cryptocurrency (IACR) among the potential investors of Pakistan.Design/methodology/approachThe theory of planned behavior (TPB) is applied to underpin the conceptual framework. The study uses a quantitative approach. The study collects cross-sectional data through an online survey questionnaire. In the last, the authors utilized 334 samples for ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 76 publications
2
22
0
3
Order By: Relevance
“…Previous research indicated that perceived trust influences consumers' intention to use cryptocurrencies [32], [33], [36], [39], [62]. However, Mendoza-Tello et al [5] found that trust is not among strong predictors of cryptocurrency use, possibly due to a lack of adequate understanding at early stages of disruptive technologies.…”
Section: Hypotheses Development a Consumer Trust In Crypto-payment An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicated that perceived trust influences consumers' intention to use cryptocurrencies [32], [33], [36], [39], [62]. However, Mendoza-Tello et al [5] found that trust is not among strong predictors of cryptocurrency use, possibly due to a lack of adequate understanding at early stages of disruptive technologies.…”
Section: Hypotheses Development a Consumer Trust In Crypto-payment An...mentioning
confidence: 99%
“…The technology acceptance model (TAM) has been the mostly cited theory in studying antecedents of cryptocurrency adoption (e.g., [33], [34]). Other well-known adoption theories, such as the theory of planned behavior (TPB), have also been applied in this domain (e.g., [35], [36]). These studies highlighted relevant factors to cryptocurrency adoption such as individuals' perceptions about usefulness and ease of using the technology as well as their subjective norms.…”
Section: B Consumer Adoption Of Cryptocurrenciesmentioning
confidence: 99%
“…Huong et al Although (2021) concluded that PBC has a negative effect on crypto-asset investment intention, in this study, as in many other studies (Schaupp at al., 2022 ; Soomro et al, 2022 ; Mazambani & Mutambara, 2019 ) It has been determined that it has a positive effect on the attitude and it is the second factor that determines the intention after the attitude. This result means that investors have sufficient knowledge, skills, resources and confidence to invest in crypto assets.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the use of crypto-assets have shown that positive attitudes affect the investment intention towards crypto-assets (Schaupp et al, 2022 ; Soomro et al, 2022 ; Mazambani & Mutambara, 2019 ). From this point of view, the hypothesis established to investigate the effect of attitude on the intention to adopt crypto-asset investments in Turkey is as follows.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In fact, TPB used to clarify an individual's intention to perform a given behavior. Additionally, TPB has also been used broadly in explaining EI in a number of studies (AlGhani et al, 2022;Soomro et al, 2022, Krueger et al, 2000Autio et al, 2001). TPB has been shown to predict EI most accurately.…”
Section: Entrepreneurial Intentionmentioning
confidence: 99%